PEDT-12 NATIONWIDE LANDSCAPE OF GENOMIC ANALYSIS OF PEDIATRIC CENTRAL NERVOUS SYSTEM TUMORS. (3rd December 2022) - Watanabe, Yuko; Takahashi, Masamichi; Koyama, Takafumi; Sunami, Kuniko; Kubo, Takashi; Cho, Hourin; Hirata, Makoto; Tao, Kayoko; Sudo, Kazuki; Kohsaka, Shinji; Yanagisawa, Shunsuke; Ohno, Makoto; et al.
Abstract: Background and Purpose: In Japan, cancer-gene profiling (CGP) tests, such as the OncoGuide NCC Oncopanel System, FoundationOne CDx Cancer Genome Profile (F-one), and FoundationOne Liquid CDx Cancer Genome Profile, are covered by insurance and clinically applied to promote cancer genomic medicine. Information from CGP tests is managed at the Center for Cancer Genomics and Advanced Therapeutics (C-CAT) and shared with clinicians after discussions at the Expert Panel (EP). We provide an overview of the registered pediatric CNS tumors. Methods: We extracted and analyzed CNS/brain data from the C-CAT registry from June 2019 to June 2022 for ages 0–19 years. Variables such as age, gender, histopathological diagnosis, CGP test type, ECOG Performance Status (PS), registration status, genetic abnormalities, and treatments were analyzed. Results: Among 1133 patients of all ages with CNS tumors, 361 (31.9%) were aged 0–19 years; Of the 918 patients aged 0-19 years with any type of cancer, those with CNS tumors accounted for 34.2%; 188 patients were aged under 10 years, 173 patients were teenagers, 174 patients were males, 187 patients were females; PS was 0 in 47.9% of patients. The most common histopathological diagnoses were medulloblastoma, diffuse midline glioma and glioblastoma. Genetic abnormalities included TP53 mutations in 85 cases, H3F3A mutations in 38 cases, STK11 mutations in 36 cases, BRAF mutations in 33 cases, BRAF-KIAA1549 fusions in 24 cases, and TMB high in 16 cases. Seventy-six patients (21.1%) were offered treatment options in the EP, and 26 patients (7.2%) received the recommended treatment, including two in physician-initiated trials, four in company trials, eleven in treatments within insurance coverage, and eleven in others. Discussion: This is the first report of genetic analysis of pediatric CNS tumors on a nationwide scale. Pediatric CNS tumors have a large number of registered cases; thus, drug development for them is urgently needed.